Foreign Language Lexicons Used in Indonesian Housing Names: A Peircean Semiotics Overview - Chusni Hadiati (Soegijapranata Catholic University, 2020)
Abstract: Housing belongs to human basic need since to live properly they need a place to stay. Housing names in Indonesia employ not only Bahasa Indonesia but also foreign language because some foreign lexicons are used in Indonesian housing names. Semiotically, names are symbols that carry meaning in certain context. Indonesian housing names are interesting language phenomena since they reveal the use of language as a social praxis. Legally, the use of language in public space is governed by Indonesian Law No.24, Year 2009 on flag, language, national symbols, and national anthem. In fact, Indonesian housing names do not fully follow the law because foreign language lexicons are also used in Indonesian housing names. This research employed 2000 Indonesian housing names and collected during January 2017 until May 2017. Data indicated that there were lexicons from three foreign languages, namely, English, Spanish, and Arabic. This research belongs to descriptive qualitative research. In-depth interview was also utilized to gain deeper information why developers use certain lexicons. Developers believed that names are supposed to be beneficial and bring luck. Using Peircean semiotic, this qualitative research reveals that lexicons used in Indonesian housing names are used to show place name (Baturraden, Citayam, Batam, Surabaya), settlement (cassa, village, residence, estate, city, garden, hill, valley, river, lake), greatness (grand, grande, great, royal, big), positivity (blossom, lucky, oase, firdaus, sakinah, paradise), preciousness (emerald, platinum, diamond, golden, stone), environmental awareness (green color), purity (white color, jasmine), warmth (red rose), and love (red color, orchid, lily, tulip).